Forecasting the Impacts of Silver and Bighead Carp on the Lake Erie Food Web. Issue 1 (2nd January 2016) - Zhang, Hongyan; Rutherford, Edward S.; Mason, Doran M.; Breck, Jason T.; Wittmann, Marion E.; Cooke, Roger M.; Lodge, David M.; Rothlisberger, John D.; Zhu, Xinhua; Johnson, Timothy B.
Abstract: Nonindigenous bigheaded carps (Bighead Carp Hypophthalmichthys nobilis and Silver Carp H. molitrix ; hereafter, "Asian carps" [AC]) threaten to invade and disrupt food webs and fisheries in the Laurentian Great Lakes through their high consumption of plankton. To quantify the potential effects of AC on the food web in Lake Erie, we developed an Ecopath with Ecosim (EwE) food web model and simulated four AC diet composition scenarios (high, low, and no detritus and low detritus with Walleye Sander vitreus and Yellow Perch Perca flavescens larvae) and two nutrient load scenarios (the 1999 baseline load and 2× the baseline [HP]). We quantified the uncertainty of the potential AC effects by coupling the EwE model with estimates of parameter uncertainty in AC production, consumption, and predator diets obtained using structured expert judgment. Our model projected mean ± SD AC equilibrium biomass ranging from 52 ± 34 to 104 ± 75 kg/ha under the different scenarios. Relative to baseline simulations without AC, AC invasion under all detrital diet scenarios decreased the biomass of most fish and zooplankton groups. The effects of AC in the HP scenario were similar to those in the detrital diet scenarios except that the biomasses of most Walleye and Yellow Perch groups were greater under HP because these fishes were buffered from competition with AC by increased productivity at lower trophic levels. Asian carp predation on Walleye and Yellow Perch larvae caused biomass declines among all Walleye and Yellow Perch groups. Large food web impacts of AC occurred in only 2% of the simulations, where AC biomass exceeded 200 kg/ha, resulting in biomass declines of zooplankton and planktivorous fish near the levels observed in the Illinois River. Our findings suggest that AC would affect Lake Erie's food web by competing with other planktivorous fishes and by providing additional prey for piscivores. Our methods provide a novel approach for including uncertainty into forecasts of invasive species' impacts on aquatic food webs. Received December 6, 2014; accepted July 15, 2015